The Misplaced Confidence of The Common Man in Julius Caesar - Sami ul Haq (University of Chitral Journal of Linguistics and Literature, 2024)
The research article shows the force of rhetorical language and its powerful impact upon the masses when they are a crowd through the speeches of Brutus and Antony to the people of Rome in Julius Caesar by the Elizabethan dramatist, William Shakespeare. The article draws on the textual analysis as primary source, and modern critical body as a secondary source. It shows how Shakespeare remains a dramatist of the highest order by virtue of his psychological understanding about the generality that we have today with the same conceptual framework. The misplaced confidence on populist, demagogue, and an authoritarian person culminates in the killing of an innocent person, Cenna, with the establishment of anarchy. This work tries to show the general perception of the masses their own troubles that are always ignored in the government.